Liberia : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver and Modification of Performance Criteria, and Financing Assurances Review; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2009)
The drop in demand and commodity prices in Liberia is adversely affecting investment and exports in some key sectors. The staff report examines Liberia's second review under the Poverty Reduction and Growth Facility and request for Waiver and Modification of Performance Criteria. The global recession is slowing Liberia's post-war economic recovery. There is limited room for countercyclical fiscal action owing to high debt levels while monetary policy is constrained by high dollarization. In the mining sector, investment continues, and iron ore exports are expected to resume with the global economic recovery.